Improved synthesis of [18F]FS-PTAD as a new tyrosine-specific prosthetic group for radiofluorination of biomolecules. (October 2015) - Al-Momani, Ehab; Israel, Ina; Buck, Andreas K.; Samnick, Samuel
Abstract: A novel prosthetic group, 4-(p-([ 18 F]fluorosulfonyl)phenyl)-1, 2, 4-triazoline-3, 5-dione ([ 18 F]FS-PTAD) for site-specific radiofluorination of tyrosine residue in small molecules is described. Coupling of [ 18 F]FS-PTAD with L-tyrosine, N-acetyl-L-tyrosine methyl amide and phenol as model compounds were achieved in buffered aqueous solution at room temperature, resulting in the corresponding fluorinated tyrosine and phenol derivatives. The total synthesis time including radiosynthesis, HPLC purification and formulation was less than 60 min ( n =15) with ≥98% radio chemical purity. An initial in vitro evaluation of [ 18 F]FS-PTAD-tyrosine in glioma cell lines revealed moderate uptake. Graphical abstract: Highlights: We developed a novel prosthetic group, [ 18 F]FS-PTAD, for labeling tyrosine residue. PTAD was radiofluorinated using sulfonyl chloride precursor without azeotropic drying. [ 18 F]FS-PTAD was obtained in 91±0.9% RCY using CsCO3 and MeCN as at RT. The coupling was performed under mild conditions resulting in 40–60% RCY ( n =15).